Reduction of Wastage Construction Material during Execution Phase: Improving Construction Material Management for Sustainable Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Now days, the increased economic growth as well as urbanization in developing countries have led into extensive construction activities that generate large amounts of wastes. Material wastage in construction projects resulted into huge financial setbacks to builders and contractors. In addition to this, it may also cause significant effects over aesthetics, health, and the general environment. These wastes needs to be managed as well as their impacts needs to be ascertained to pave way for their proper management, however in many cities of India wastes materials management is still a problem. In this research work we are discussing the method for the management and control of waste construction materials. The main objective of this work is present the waste control procedures included as part of particular site management in general based on pull learning process and focusing process transparency principle based on qualitative and quantitative data collection techniques. Additionally we are presenting the literature survey study over waste management system as well as construction waste management